PERANAN BALAI PEMASYARAKATAN (BAPAS) DALAM MELAKUKAN BIMBINGAN KEMASYARAKATAN TERHADAP NARAPIDANA YANG MEMPEROLEH PEMBEBASAN BERSYARAT DITINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Dian Ekawati (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTHall of Corrections (BAPAS) is to implement the guidance of social institutions. In accordance with Act 12 of 1995 undangNomor supervising civic duty contained in Article 2 paragraph 1 of the Decree of the Minister of Justice No. M.01-PK.04.10 In 1998, one of which is to implement the guidance of social and vocational guidance for correctional clients. Especially with the aim that the client is not willing to commit acts criminal offenses in the future. However, in the implementation of the work in the body BAPAS experienced internal and external constraints.The purpose of writing this essay for Social Research to examine the implementation by BAPAS Class II Samarinda proposed for inmates to obtain parole, knowing Role BAPAS Class II Samarinda in implementing the guidance of the Correctional Clients who obtain parole is later called correctional clients, and to identify constraints -kendala faced BAPAS Class II Samarinda in the framework of the implementation of the guidance to the Client of Corrections who obtain parole. Results showed that task Correctional Center is for healing and rehabilitation and social reintegration of the offenders to be able to adjust to life back in the community. Keywords: Parole, Research Society.